Analisis Peran Badan Permusyawaratan Desa dalam Sistem Pemerintahan Desa di Indonesia - Tohawi, Agus (Bahasa Indonesia, 2025)
The Village Consultative Body (Badan Permusyawaratan Desa/BPD) plays a pivotal role in strengthening democratic and participatory village governance in Indonesia. As a legislative institution at the village level, the BPD is responsible for channeling community aspirations, formulating regulations, and overseeing the performance of village heads and the use of Village Funds. However, the effectiveness of the BPD faces challenges such as limited member capacity, political intervention from local elites, and non-inclusive participation, particularly from women and youth. Case studies in Panggungharjo Village (Yogyakarta) and Tenganan Village (Bali) demonstrate that collaboration between the BPD, communities, and traditional institutions, coupled with technology-driven transparency, can enhance accountability and development quality. Strategic recommendations include capacity-building through technical training, regulatory reforms to reinforce BPD independence, and affirmative policies for marginalized groups. With a holistic approach, the BPD can become a catalyst for equitable and sustainable village development.